Residual biomass saccharification in processing tomato is affected by cultivar and nitrogen fertilization. (January 2015) - Ercolano, M.R.; Gomez, L.D.; Andolfi, A.; Simister, R.; Troise, C.; Angelino, G.; Borrelli, C.; McQueen-Mason, S.J.; Evidente, A.; Frusciante, L.; Caruso, G.
Abstract: Two processing tomato hybrids and five N fertilization rates were evaluated regarding their biomass, fruit yield, and saccharification potential. Although no difference was detected between the hybrids, both for fruit and residual biomass yield, 106 kg ha −1  N fertilization rate showed the highest fruit mass and 186 kg ha −1 resulted in the highest residual biomass production. The biomass in the hybrid Kero had higher content of total and crystalline cellulose compared to Defender. N fertilization significantly changed biomass composition. Eighty kg ha −1 N led to the highest lignin, hemicellulose and pectin content, whereas the 159 kg ha −1 applications caused the highest percentage of total and crystalline cellulose. Xylose was the most abundant monosaccharide in hemicelluloses, whereas fucose was the lest abundant. The hybrid Kero gave higher ethanol potential production than Defender and both hybrids reached the highest values under 159 kg ha −1 of N. Alkali pre-treatment caused the highest values of saccharification and hot water the lowest. The hybrid Kero showed higher saccharification potential than Defender and 159 kg ha −1  N fertilization rate led to the best results. We show that tomato residual biomass is an interesting lignocellulosic feedstock for ethanol production and both hybrid and nitrogen fertilization rate significantly affects the biomass chemical composition and saccharification potential of the residual biomass. Highlights: Interaction between hybrid and nitrogen fertilization had a significant effect on theoretical ethanol yield. Saccharification was positively correlated with total and crystalline cellulose. Alkali pretreatment resulted in the highest biomass enzymatic digestibility efficiency. Hybrid and nitrogen fertilization increase significantly modified biomass quality.